Could dexmedetomidine be repurposed as a glymphatic enhancer? - Persson Niklas Daniel Åke; Uusalo Panu; Nedergaard Maiken; Lohela Terhi J; Lilius Tuomas O (ELSEVIER SCIENCE LONDON, 2025)
Cerebrospinal fluid (CSF) flows through the central nervous system (CNS) via the glymphatic pathway to clear the interstitium of metabolic waste. In preclinical studies, glymphatic fluid flow rate increases with low central noradrenergic tone and slow-wave activity during natural sleep and general anesthesia. By contrast, sleep deprivation reduces glymphatic clearance and leads to intracerebral accumulation of metabolic waste, suggesting an underlying mechanism linking sleep disturbances with neurodegenerative diseases. The selective alpha(2)-adrenergic agonist dexmedetomidine is a sedative drug that induces slow waves in the electroencephalogram, suppresses central noradrenergic tone, and preserves glymphatic outflow. As recently developed dexmedetomidine formulations enable self-administration, we suggest that dexmedetomidine could serve as a sedative-hypnotic drug to enhance clearance of harmful waste from the brain of those vulnerable to neurodegeneration.